2016
DOI: 10.5194/piahs-374-175-2016
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated method for long-term water quality prediction using seasonal climate forecast

Abstract: The APEC Climate Center (APCC) produces climate prediction information utilizing a multi-climate model ensemble (MME) technique. In this study, four different downscaling methods, in accordance with the degree of utilizing the seasonal climate prediction information, were developed in order to improve predictability and to refine the spatial scale. These methods include: (1) the Simple Bias Correction (SBC) method, which directly uses APCC's dynamic prediction data with a 3 to 6 month lead time; (2) the Moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…MBC also leads to spatial downscaling of the original model forecasts from GCMs (2.5 • × 2.5 • ) into the high resolution of the ERA5-Land (0.1 • × 0.1 • ), which enabled more location-specific application of SCFs in our study. Using the bias-corrected forecasts' monthly means of temperature and precipitation variables, we subsequently selected a best-fit historical observation data, in this case from the ERA5-Land reanalysis data for 30 years of 1981-2010, based on the Mahalanobis Distance (MD) (Cho et al, 2016). Similar analog sampling from historical observation data has been frequently used for the downscaling of GCM data for subsequent applications (Hirschi et al, 2012;Wu et al, 2012).…”
Section: Seasonal Climate Forecasts and Downscalingmentioning
confidence: 99%
“…MBC also leads to spatial downscaling of the original model forecasts from GCMs (2.5 • × 2.5 • ) into the high resolution of the ERA5-Land (0.1 • × 0.1 • ), which enabled more location-specific application of SCFs in our study. Using the bias-corrected forecasts' monthly means of temperature and precipitation variables, we subsequently selected a best-fit historical observation data, in this case from the ERA5-Land reanalysis data for 30 years of 1981-2010, based on the Mahalanobis Distance (MD) (Cho et al, 2016). Similar analog sampling from historical observation data has been frequently used for the downscaling of GCM data for subsequent applications (Hirschi et al, 2012;Wu et al, 2012).…”
Section: Seasonal Climate Forecasts and Downscalingmentioning
confidence: 99%
“…Improvements in impact models themselves may also be required as, in some cases, errors derived from impact models may be the dominant source of uncertainty (e.g. Cho et al, 2016). However, probably the greatest potential here is through improved/increased data collection.…”
Section: Future Priorities For More Skilful Seasonal Predictionsmentioning
confidence: 99%
“…Meanwhile, seasonal forecasts of water quality and ecology are rare, despite their potential relevance for management. The few examples we could find included river nutrient loads in a Korean catchment (Cho et al, 2016) and turbidity exceedance in a drinking water source in the Pacific Northwest (Towler et al, 2010), and while both studies focused primarily on method development, Towler et al (2010) showed that their workflow, which incorporated seasonal climate forecasts, resulted in an improvement in skill over climatology.…”
mentioning
confidence: 99%
“…The few examples we could find included river nutrient loads in a Korean catchment (Cho et al, 2016) and turbidity exceedance in a drinking water source in the Pacific Northwest (Towler et al, 2010), both of which showed promising results. For standing waters, the use of short-term weather forecasts, i.e.…”
Section: Introductionmentioning
confidence: 99%